\(\frac{4}{15}+\frac{8}{13}+\frac{11}{15}+\frac{5}{13}\)
\(=\left(\frac{4}{15}+\frac{11}{15}\right)+\left(\frac{8}{13}+\frac{5}{13}\right)\)
\(=\frac{15}{15}+\frac{13}{13}\)
\(=1+1\)
\(=2\)
Chúc bạn học tốt nha !!!
\(\frac{4}{15}+\frac{8}{13}+\frac{11}{15}+\frac{5}{13}\)
\(=\left(\frac{4}{15}+\frac{11}{15}\right)+\left(\frac{8}{13}+\frac{5}{13}\right)\)
\(=1+1\)
\(=2\)
=(4/15+11/5)+(8/13+5/13)
=37/15+1=52/15
k mink nha
Sorry bn.Mk nhầm nha
Theo mk : nguyen thi thu đúng rồi
=/
\(\frac{4}{15}\)+ \(\frac{8}{13}\)+ \(\frac{11}{5}\)+ \(\frac{5}{13}\)
= ( \(\frac{4}{15}\)+ \(\frac{33}{15}\)) + ( \(\frac{8}{13}\)+ \(\frac{5}{13}\))
= \(\frac{37}{15}\)+ \(\frac{13}{13}\)
= \(\frac{37}{15}\)+ 1
=\(\frac{37}{15}\)+ \(\frac{15}{15}\)
= \(\frac{52}{15}\)
\((\)\(\frac{8}{13}\)+\(\frac{5}{13}\)\()\)+\((\)\(\frac{4}{15}\)+\(\frac{33}{15}\)\()\)
= 1 + \(\frac{37}{15}\)
= 1+1+1+\(\frac{7}{15}\)
= 3+\(\frac{7}{15}\)
= 3\(\frac{7}{15}\)